# If x=4

If x=4 and y=-3, what is the value of the expression x² + 2xy - 4x + 3y + y²?

### Correct answer:

#### You need to know the following knowledge to solve this word math problem:

## Related math problems and questions:

- Variables: 3140

Determine the value of the expression 3a + 2b - a ^ 2 - 4b ^ 2 for the values of the variables: a) a = - 1, b = 3 b) a = 2, b = -1 c) a = -2, b = -3 d) a = 4, b = 2 e) a = -5, b = 0 - Expressions 3

If k(x+6)= 4x² + 20, what is k(10)=? - Calculate 25111

The quadratic function has the formula y = -2x²-3x + 8. Calculate the function value in points 5, -2 and ½. - What is 10

What is the measure of the square side whose area is (4x² + 28x+49) square units? - Trapezoid 15

Area of trapezoid is 266. What value is x if bases b1 is 2x-3, b2 is 2x+1 and height h is x+4 - Completing square

Solve the quadratic equation: m^{2}=4m+20 using completing the square method - Expression 4451

Find the largest natural number d that has that property for any natural number the number n is the value of the expression V (n) = n ^ 4 + 11n ^ 2−12 is divisible by d. - Evaluate expr with 2 vars

If a=6 and x=2, find the value of (2ax + 7x- 10) /(4ax-3a-2) - Find the 2

Find the term independent of x in the expansion of (4x^{3}+1/2x)^{8} - Center

Calculate the coordinates of the circle center: x² -4x + y² +10y +25 = 0 - Substituting 3165

Determine the value of the expression by substituting for the variables a = 5, b = 2, x = 3, y = 1: k = 4ab + 1/2 ab - 14 l = x² + 2xy + y² m = 5b³ - 4b^{2} - Expressions

Find out value of expressions if a = -1, b =2: x=b - 2a - ab y=a³ - b² - 2ab z=a² b³ - a³ b² w=a + b + a³ - b^{2} - Determine 4104

Determine the value of x in this equation: (0.125^x) · 10^{4}= 5000 - Square root 2

If the square root of 3m² +22 and -x = 0, and x=7, what is m? - Evaluate 5

Evaluate expression x^{2}−7x+12x−4 when x=−1 - Two expressions

When x = 3 and y = 5, by how much does the value of 3x² – 2y exceed the value of 2x² – 3y? - Polynomial 6321

Simplify polynomial entry: (x + 2)² + (x-2) (x + 2)